Does cigarette smoking increase a risk of type 2 diabetes mellitus development? - Pekar, Joanna; Skolarczyk, Justyna Magdalena; Tadla, Monika; Jóźwiak, Aleksandra; Olszewska, Anna; Skórzyńska-Dziduszko, Katarzyna (Journal of Education, Health and Sport, 2017)
Introduction. The Finnish Diabetes Risk Score (FINDRISC) questionnaire is a screening tool used to estimate the 10-year risk of type 2 diabetes in adults by identifying individuals with overweight or obesity, inadequate physical activity, poor nutrition, or a family or personal history of hyperglycemia. Aim. The objective of the study was to analyze the incidence of cigarette smoking in randomly selected individuals screened with FINDRISC scale, and the effect of nicotinism on body weight, waist circumference, the magnitude of arterial pressure, and the total FINDRISC scores. Material and methods. The study was conducted in 2016 in Lublin on 99 individuals – 51 women and 48 men. We determined FINDRISC score and measured blood pressure twice. The results were analyzed in STATISTICA 10 at p < 0.05. Results. Only 12 individuals (12.12% of total 99 subjects; 7 females and 5 males) declared heavy smoking. Surprisingly, body mass index (BMI), waist circumference, systolic and diastolic arterial pressure values, and total FINDRISC values did not significantly differ between heavy smokers and non-smokers. Conclusions. A low incidence of nicotinism in the examined population proves an effectiveness of a public program encouraging to non-smoking. In opposition to common beliefs, nicotinism is not an efficient tool for weight reduction. The diabetes risk seems to be not increased by cigarette smoking; however this result should be confirmed in a study on the larger group of patients.